2021
DOI: 10.3389/fneur.2021.715428
|View full text |Cite
|
Sign up to set email alerts
|

Gender Gap in Neurology Research Authorship (1946–2020)

Abstract: Gender disparity in the field of neurology impedes scientific advancements and innovations. In 2018, 45.0% of neurology and neurological subspecialty residents were women. Despite a notable rise in the proportion of women neurologists over the past decades, inequalities regarding publication proportions between men and women persist in the field. This cohort study examines authorship trends in articles published in 155 international neurology journals, identified as those listed in the annual Journal Citation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 30 publications
4
12
0
Order By: Relevance
“…Moreover, despite the rising proportion of women in the field with postgraduate training in MS, their academic and leadership positions continue to be scarce; salaries are still inferior compared to men's and they are underrepresented in scientific literature. These results are aligned with those published in other countries ( 10 ). Data from the Association of American Medical Colleges showed that men outnumbered women at all levels in academic neurology programs (professor: 13%; associate professor: 30%; assistant professor: 43%; and instructor: 40%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, despite the rising proportion of women in the field with postgraduate training in MS, their academic and leadership positions continue to be scarce; salaries are still inferior compared to men's and they are underrepresented in scientific literature. These results are aligned with those published in other countries ( 10 ). Data from the Association of American Medical Colleges showed that men outnumbered women at all levels in academic neurology programs (professor: 13%; associate professor: 30%; assistant professor: 43%; and instructor: 40%).…”
Section: Discussionsupporting
confidence: 92%
“…A study was done in Canada and the United States examined the authorship trends in neuroscience literature and found that men dominate first and last authorship. Furthermore, they found that men as the last authors were more likely to be published ( 10 ). The gender gap is also apparent within the pharmaceutical companies, which lead phase 3 trials in multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…This trend corroborates the results of two literature studies: in neurology by Nguyen et al (236) and in neuroscience by Dworkin et al (237). In the first study, the authors noted the increase of female authorship in journals classified in the MeSH Journal Category "Pain" from 7.6% to 35.4% in 2002-2020 (236). Although this positive trend is certainly encouraging and heading towards parity, a recent study revealed a highly skewed gender disparity in the publications of the pain research community with a prevalence of 70.6% male first authors and 81.6% male senior authors (176).…”
Section: Journal Impact Factor (Jif) or Impact Factor (If)supporting
confidence: 93%
“…Two decades later, in a brief commentary, an impressive increase of the percentage of female authors in pain-related publications from 26.4% in 2005 to 40.5% in 2015 was noted by Szilagyi and Bornemann-Cimenti (171). This trend corroborates the results of two literature studies: in neurology by Nguyen et al (236) and in neuroscience by Dworkin et al (237). In the first study, the authors noted the increase of female authorship in journals classified in the MeSH Journal Category "Pain" from 7.6% to 35.4% in 2002-2020 (236).…”
Section: Journal Impact Factor (Jif) or Impact Factor (If)supporting
confidence: 86%
“…This naturally leads to fewer self-citations for women, and it may reflect that women are less extensively included in co-authorship networks than men 27,28 . These self-citation and authorship discrepancies could contribute to the "leaky pipeline" of women in STEM 29 , which contributes to disparities in academic faculty positions [30][31][32] , editorial boards 33 , and awards 34 . Nevertheless, future work is needed to determine if and how lower self-citation rates contribute to these outcomes.…”
Section: Gender Disparities In Self-citation Ratesmentioning
confidence: 99%